Heavy metals and their impact on surface waters of the Mantaro river basin, Junin, Peru - Chira Fernández, Jorge Eduardo (2022)
In the Mantaro river basin, located in Central Peru, an agricultural activity developed, even supplying the capital of Peru. An intense mining activity took place in the headwaters of this basin, and the La Oroya Metallurgical Complex was built a century ago. Mining activity has left mining environmental liabilities, which directly impact the quality of the water and the soil. In this sense, it is very important to investigate the presence of heavy metals and identify the geochemical associations present in surface waters to assess the real impact on the environment. For this purpose, 30 water samples were analyzed, collected from the Mantaro River and the channels that derive water for irrigation and animal consumption. The samples were analyzed by ICP-MS techniques, inductively coupled plasma-mass spectrometry, and ICP-AES, inductively coupled plasma-optical emission spectrometry. For the evaluation of the main physicochemical parameters, the ECA has been used, as the environmental quality standard of Peru, according to the Ministry of the Environment (2017); while for the chemical quality of surface water, the quality standards of the WHO, World Health Organization, were taken as a reference, according to the WHO guide (2017), being the elements considered: Al, As, Mn, Pb, and Zn. Investigations results show that the waters of some sectors have concentrations of As and Pb, which exceed the standards established by WHO, and there are also some specific cases (Muqui canal) in which Al and Mn exceed the WHO standard. In the case of Zn, its concentrations are much lower than the WHO standard.